PECULIARITIES OF ADAPTIVE PHYSICAL EDUCATION, ITS ROLE IN SOCIETY, IMPORTANCE - Aminov Botir Umidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article clearly and scientifically explains the peculiarities of adaptive physical education, its role in society, its importance. Also, on the basis of instructions on the content, structural and organizational aspects of adaptive physical rehabilitation, instructions for improving the quality of life and health of human adaptation (adaptation), adaptive (adaptive) physical activity, adaptive physical culture, adaptive physical education and adaptive sports sensorimotor and intellectual disabilities are expressed.